Lettering and Signage in the Urban Environment of North Queensland’s Capital: Tropical Flair or Univernacular? - Katja Fleischmann (eTropic: electronic journal of studies in the tropics, 2011)
Many typefaces possess next to stylistic qualities also cultural and connotative properties. This paper describes an exploration of signage and lettering in the capital of North Queensland in the quest for a tropical typographic resonance. Is the vernacular typography alive or a vanishing art form?